Heteromeles Arbutifolia, a Traditional Treatment for Alzheimer’s Disease, Phytochemistry and Safety - Xiaogang Wang; Raphael Dubois; Caitlyn Young; Eric J. Lien; James D. Adams (Medicines, 2016)
Background: This study examined the chemistry and safety of Heteromeles arbutifolia, also called toyon or California holly, which is a traditional California Indian food and treatment for Alzheimer’s disease. Methods: Plant extracts were examined by HPLC/MS, NMR and other techniques to identify compounds. Volunteers were recruited to examine the acute safety of the plant medicine using a standard short-term memory test. Results: The plant was found to contain icariside E4, dihydroxyoleanenoic acid, maslinic acid, betulin, trihydroxyoxo-seco-ursdienoic acid, catechin, vicenin-2, farrerol, kaempferide and tetrahydroxyoleanenoic acid. These compounds are anti-inflammatory agents that may protect the blood-brain barrier and prevent inflammatory cell infiltration into the brain. The dried berries were ingested by six volunteers to demonstrate the safety of the medicine. Conclusion: The plant medicine was found to contain several compounds that may be of interest in the treatment of Alzheimer’s disease. The plant medicine was found to be safe.